The Effect of land uses on physicochemical water quality at three rivers in Sungai Endau watershed, Kluang, Johor, Malaysia. - Aweng Eh Rak; Ismid Said; Maketab Mohamed (2011)
This study was conducted to determine physical and chemical water quality for three rivers which flowed through different land uses. Water quality was surveyed from November 2008 to June 2010 at five identified stations which were located at three rivers in Sungai Endau watershed (Dengar, Madek and Mengkibol river) Kluang, Johor. There were two types of data obtained from the river water quality sampling exercise, i.e. in-situ and laboratory analyses data. A total of five water quality parameters were measured namely pH, dissolved oxygen, conductivity, temperature and turbidity by using a multi parameters probe Model YSI 6920 with 650 MDS Display/Logger as well as single parameter probe. While, for laboratory analysis, there were seven parameters measured; namely Biochemical oxygen Demand (BOD), Suspended Solid (SS), Phosphate, Nitrate and Sulphate, Chemical Oxygen Demand (COD) and Ammoniacal Nitrogen (AN). Based on the results, it was found that Mengkibol river (urban river) recorded high conductivity, temperature, salinity, turbidity, COD, BOD5, ammoniacal nitrogen, nitrate, phosphate and total suspended solid, while Madek (logging) and Dengar (oil palm plantation) stations including the reference (Hulu Dengar) and back-up reference stations (Gunung Berlumut) recorded high DO concentrations and at the same time and there was no distinct variation between stations for pH. The Water Quality Index (WQI) results for all the rivers were under class I & II except Mengkibol river that was under class III when compared with the Malaysian’s WQI guideline. Key words: